Large cities lose their growth advantage as countries urbanize - Andrea Musso; Diego Rybski; Dirk Helbing; Frank Neffke (Proceedings of the National Academy of Sciences, 2026)
The share of the world population living in cities with more than one million people rose from 11% in 1975 to 24% in 2025 (our estimates). Will this trend toward greater concentration in large cities continue or level off? We introduce two new city population datasets that use consistent city definitions across countries and over time. The first covers the world between 1975 and 2025, using satellite imagery. The second covers the United States between 1850 and 2020, using census microdata. We find that urban growth follows a characteristic life cycle. In the early stages of a country’s urbanization process, large cities grow faster than smaller ones. At later stages, growth rates equalize across sizes. We use this life cycle to project future population concentration in large cities. Our projections suggest that 38% of the world population will be living in cities with more than one million people by 2100. This estimate is higher than the 33% implied by the well-known theory of proportional growth, but lower than the 42% obtained by extrapolating current trends.